International entrepreneurship - Rugman, Alan M.; Wright, Richard W. (Research in global strategic management, 1999)
The focus of this volume is the phenomenon of globalization, and specifically its relevance to and impact on small business and entrepreneurship. The works presented here stem from a pioneering, three day conference held at McGill University in Montreal, Canada, under the joint auspices of McGill's Centre for International Business Studies, and the Dobson Centre for Entrepreneurial Studies. Leading international scholars came together to begin integrating research in what had previously been from widely divergent fields. The book presents four sections covering: theoretical overviews of the emerging field of international entrepreneurship; the use of alliances and networks to facilitate the entry of small businesses into the global arena; the results of three empirically based research studies designed to better understand the market forces and managerial characteristics which appear to underlie the success of SME's in the global arena; and visionary contributions on forces which will shape the successful international firm of the future. The diversity reflected in this volume and the common thread which unites the work calls for new strategic approaches by small firms, large firms, and governments alike. This work will help readers to better understand and anticipate the dramatic changes coming, and to design appropriate corporate strategic responses.